2018
DOI: 10.1002/rth2.12088
|View full text |Cite
|
Sign up to set email alerts
|

MMP‐13 binds to platelet receptors αIIbβ3 and GPVI and impairs aggregation and thrombus formation

Abstract: Essentials MMP‐13 has the potential to influence platelet function and thrombus formation directly.We sought to elucidate whether MMP‐13 is able to bind to specific platelet receptors.MMP‐13 is able to bind to platelet alphaIIbbeta3 (αIIbβ3) and glycoprotein (GP)VI.These interactions are sufficient to inhibit platelet aggregation and thrombus formation. BackgroundAcute thrombotic syndromes lead to atherosclerotic plaque rupture with subsequent thrombus formation, myocardial infarction and stroke. Following ru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 44 publications
0
10
0
Order By: Relevance
“…Interestingly, the targeted deletion of p66ShcA increased MMP-13 postinfarction. Unlike MMP-2 and MMP-9, MMP-13 is reported to reduce cardiac fibrosis (210) and thrombosis (210). MMP-13 is activated early and transitionally after myocardial infarction (211).…”
Section: Tlr9 Pathwaymentioning
confidence: 99%
“…Interestingly, the targeted deletion of p66ShcA increased MMP-13 postinfarction. Unlike MMP-2 and MMP-9, MMP-13 is reported to reduce cardiac fibrosis (210) and thrombosis (210). MMP-13 is activated early and transitionally after myocardial infarction (211).…”
Section: Tlr9 Pathwaymentioning
confidence: 99%
“…A number of the MMPs are noted to have catalytic activity at the platelet surface, and in the case of MMP‐2, intracellular cleavage of talin which may contribute to transmission of inside‐out signals leading to αIIbβ3 activation. Here, the mechanism of action of MMP‐13 on platelets did not seem to involve direct cleavage of GPVI or αIIbβ3. Whilst MMP‐13 could cleave recombinant purified forms of GPVI and αIIbβ3, as well as purified fibrinogen, treatment of platelets with MMP‐13 did not result in release of GPVI or αIIbβ3.…”
Section: Platelet‐associated Mmps—location Of Platelet‐associated Mmpmentioning
confidence: 75%
“…Matrix metalloproteinases (MMPs) are calcium‐dependent zinc‐containing endoproteases involved in extracellular matrix and non‐matrix protein degradation . In the latest issue of Research and Practice in Thrombosis and Haemostasis , Howes and colleagues investigated the role of MMP‐13 in platelet aggregation and thrombus formation and identified that MMP‐13 could engage important platelet receptors and influence platelet function in vitro. MMP‐13 is of great cardiovascular interest as expression of this metalloproteinase is significantly upregulated in a host of atherothrombotic and inflammatory conditions …”
Section: Platelet‐associated Mmps—location Of Platelet‐associated Mmpmentioning
confidence: 99%
See 1 more Smart Citation
“…Study by Huang et al, shows higher expression of MMP-9 in human compared to rats [22]. In vitro study by Howes et al shows MMP-13 role in platelet aggregation inhibition and thrombus formation [23]. This protease is upregulated in atherothrombotic and inflammatory conditions [24].…”
Section: Discussionmentioning
confidence: 99%